Children and Adults Working Together in the Zone of Proximal Development: A Concept for User-Centered Design - Bowler, Leanne; Large, Andrew; Beheshti, Jamshid; Nesset, Valerie (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This paper explores the theory of a zone of proximal development from the perspective of usability research and user-centered approaches to the design of information retrieval systems. Using concrete examples (dialogue, tools and techniques) from the inter-generational design teams of Large et al, this study will show how structuring usability research around Vygotsky’s theory of a zone of proximal development can offer a robust conceptual framework for eliciting responses from children on information retrieval issues and for defining the role that children can play in the design process. Cet article présente la théorie de la zone prochaine de développement à partir de la perspective de la convivialité de la recherche et des approches orientées utilisateurs pour la conception de systèmes de recherche d’information. Utilisant des exemples concrets (dialogue, outils et techniques) tirés des équipes de conception intergénérationnelles de Large et al., cette étude démontrera comment la structuration de la convivialité de la recherche autour de la théorie de la zone prochaine de développement de Vygotsky peut offrir une cadre …